A rare case of low-grade fibromyxoid sarcoma with ossification which was radiologically detected as apparent calcification and histopathologically proven - Yasuaki Tsuchida; Yoshitane Tsukamoto; Hiroyuki Futani; Shunsuke Kumanishi; Takahiro Watanabe; Noriko Kajimoto; Shohei Matsuo; Shinichi Yoshiya; Seiichi Hirota (Elsevier, 2018)
Low-grade fibromyxoid sarcoma (LGFMS) is a rare soft-tissue malignant neoplasm with a deceptively benign histological appearance and a potential for late recurrence and metastasis. LGFMS cases with significant ossification are extremely rare. To our knowledge, only three cases of LGFMS with bone formation which is detected as apparent calcification by radiological examinations and proven by histopathology have been reported. Here, we report the fourth such case. A 39-year-old female presented with a 10-year history of a painless tumor in her right buttock. Computed tomography images showed multiple foci of intratumoral calcification. A needle biopsy specimen of the tumor revealed a spindle cell neoplasm with hyalinizing/collagenous stroma and ossification. The tumor cells were immunohistochemically positive for MUC4 and the molecular analysis of the tumor detected FUS-CREB3L2 fusion. Pathological diagnosis of LGFMS was made. Total resection of the tumor with wide margins was performed, and histology of the resected sample showed multiple foci of intratumoral ossification.